ANALISIS KEMAMPUAN LITERASI DIGITAL SISWA KELAS V SD MELALUI FLIPBOOK IPAS “BUMIKU SAYANG, BUMIKU MALANG” - Rinneke Anggraeni Muffidah Sari; Dya Qurrotul A’yun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of digital technology requires digital literacy skills to be introduced from elementary education. However, students’ ability to utilize learning technology still varies, both in terms of skills and digital ethics. This study aims to analyze the digital literacy skills of fifth-grade students through the use of flipbook media in the IPAS subject “Bumiku Sayang, Bumiku Malang”. The research employed a descriptive qualitative approach involving the subject teacher and fifth-grade students at SDN Tanjung Jati 2. Data were collected through observation, structured interviews with the teacher, and in-depth interviews with three students representing different ability levels. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that most students demonstrated adequate digital skills, as shown by their ability to access and use the flipbook independently. However, digital ethics were not yet consistent, as some students opened other applications during the lesson. The use of flipbooks was proven to enhance students’ motivation and understanding, particularly regarding the concept of earthquakes. This study highlights the important role of teachers as facilitators who not only guide technical skills but also instill responsibility in digital technology usage.